commitment to information to about prices and tariffs in the relations between economicagents: a study of the texts of law n 04/02 specifying the rules applicable to commercialpracties (Numerus academy review, 2026)
This research paper aims to introduce the obligation to notify prices and tariffs inthe context of relations between economic agentes and how the algerian legislator regulates it within the framework of law no.The conclusion of our research paper is q set of results, the first of wich is toemphasize the nature of this commitment that it is a general obligation, prior tocontracting, which fall on the shoulders of every economic aid, wether it is a seller or a service provider of the customer's economic aid, related to the necessity of having a request from the customer, the letter confers an obligatory character so, where shouldheinform the economic aid of prices and tariffs by any means acceptable in the profession,the conclusion of these results was to praise the Algerian legislator for the diversificationof the penalties imposed in the event of breach of the commitment, while commenting on the value of the fine signed at the present time.